Anaerobic Capacity in Running: The Effect of Computational Method - Andersson, Erik P.; Björklund, Glenn; McGawley, Kerry (Frontiers in Physiology, 2021)
To date, no study has compared anaerobic capacity estimates computed with the maximal accumulated oxygen deficit (MAOD) method and the gross energy cost (GEC) method applied to treadmill running exercise. Purpose: Four different models for estimating anaerobic energy supply during treadmill running exercise were compared. Methods: Fifteen endurance-trained recreational athletes performed, after a 10-min warm-up, five 4-min stages at 55–80% of peak oxygen uptake, and a 4-min time trial (TT). Two linear speed-metabolic rate regression models were used to estimate the instantaneous required metabolic rate during the TT (MR_TT_req), either including (5+Y_LIN) or excluding (5-Y_LIN) a measured Y-intercept. Also, the average GEC (GEC_AVG) based on all five submaximal stages, or the GEC based on the last submaximal stage (GEC_LAST), were used as models to estimate the instantaneous MR_TT_req. The anaerobic capacity was computed as the difference between the MR_TT_req and the aerobic metabolic rate integrated over time. Results: The GEC remained constant at 4.39 ± 0.29 J∙kg-1∙m-1 across the five submaximal stages and the TT was performed at a speed of 4.7 ± 0.4 m∙s-1. Compared with the 5-Y_LIN, GEC_AVG, and GEC_LAST models, the 5+Y_LIN model generated a MR_TT_req that was 3.9% lower, with corresponding anaerobic capacities from the four models of 0.72 ± 0.20, 0.74 ± 0.16, 0.74 ± 0.15, and 0.54 ± 0.14 kJ∙kg-1, respectively (F1.07,42=13.9, P=0.002). The GEC values associated with the TT were 4.22 ± 0.27 and 4.37 ± 0.30 J∙kg-1∙m-1 for 5+Y_LIN and 5-Y_LIN, respectively (calculated from the regression equation), and 4.39 ± 0.28 and 4.38 ± 0.27 J∙kg-1∙m-1 for GEC_AVG and GEC_LAST, respectively (F1.08,42=14.6, P<0.001). The absolute typical errors in anaerobic capacity ranged between 0.03-0.16 kJ∙kg-1 for the six pair-wise comparisons and the overall standard error of measurement was 0.16 kJ∙kg-1. Conclusions: These findings demonstrate a generally high disagreement in estimated anaerobic capacities between models and show that the inclusion of a measured Y-intercept in the linear regression (i.e., 5+Y_LIN) is likely to underestimate the MR_TT_req and the GEC associated with the TT, and hence the anaerobic capacity during maximal 4-min treadmill running.